Micromechanical study on the effective elastic moduli of polymer-bonded explosives with imperfect interfaces. Issue 3 (3rd July 2018) - Wang, Jingcheng; Luo, Jingrun
ABSTRACT: The particle/binder interfaces are wide spread since the particle volume fractions of polymer-bonded explosives (PBXs) are normally greater than 80%. Interfacial imperfection extensively exists and counts for the decline in effective properties. To investigate the impact of imperfect interfaces on the effective properties, a spring-interface model is introduced into the Mori–Tanaka method. Then the generalized self-consistent method is revised to predict the effective elastic moduli of PBXs. Results show that interfacial parameters have evident influences on the effective moduli. The effective modulus reduces as the interfacial imperfection aggravates, and this reduction is bigger in higher particle volume fraction. Further analyses indicate that, for PBXs, the shear moduli are independent of the interfacial normal compliance just as the bulk moduli independent of the tangential compliance. Since declines of the effective elastic moduli almost all result from the additional strain caused by imperfect interfaces, influences of the modified Eshelby tensors are negligible.